PENGARUH METODE PENYIMPANAN BENIH DAN PESEMAIAN TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN fistulosum (Allium L.) - , ADITYA MANGGALA P.; , Dr. Ir. Endang Sulistyaningsih, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Good technology of seed storage will give advantage for farmer and merchant because it can increase the economic value and seed viability. The research aims were 1) to determine the effect of seed storage and nursery methods to the growth and yield of Japanese bunching onion and 2) to determine the optimal seed storage and nursery methods to increase the productivity of Japanese bunching onion. The research was composed in two activities. First, the laboratory research was designed in completely randomized design (CRD) single factor with three treatments, namely the seed storage methods with fumigation, silica gel, and aluminum foil. Second, the field research was designed in randomized complete block design (RCBD) factorial with three blocks as replication. The first factors were the nursery methods, namely bed and polybag nursery methods. The second factors were the seed storage methods, namely the seed storage methods with fumigation, silica gel, and aluminum foil. The observations were on several variables of seed germination, growth and yield of onion leaf. Data were analyzed with Analysis of Variance (ANOVA) at 5% level, and continued with Duncan's Multiple Range Test (DMRT). The results showed methods of fumigation, silica gel and aluminum foil methods could be used in the storage of Japanese bunching onion seed. Japanese bunching onion seed nursery using polybag nursery method produced higher seedling vigor at the time of transplanting and provided higher yield when compared to bed nursery method.